OX40 blockade inhibits house dust mite driven allergic lung inflammation in mice and in vitro allergic responses in humans. Issue 4 (21st January 2015) - Burrows, Katie E.; Dumont, Celine; Thompson, Clare L.; Catley, Matthew C.; Dixon, Kate L.; Marshall, Diane
<x xml:space="preserve">Abstract</x> The costimulatory receptor OX40 is expressed on activated T cells and regulates T‐cell responses. Here, we show the efficacy and mechanism of action of an OX40 blocking antibody using the chronic house dust mite (HDM) mouse model of lung inflammation and in vitro HDM stimulation of cells from HDM allergic human donors. We have demonstrated that OX40 blockade leads to a reduction in the number of eosinophils and neutrophils in the lavage fluid and lung tissue of HDM sensitized mice. This was accompanied by a decrease in activated and memory CD4+ T cells in the lungs and further analysis revealed that both the Th2 and Th17 populations were inhibited. Improved lung function and decreased HDM‐specific antibody responses were also noted. Significantly, efficacy was observed even when anti‐OX40 treatment was delayed until after inflammation was established. OX40 blockade also inhibited the release of the Th2 cytokines IL‐5 and IL‐13 from cells isolated from HDM allergic human donors. Altogether, our data provide evidence of a role of the OX40/OX40L pathway in ongoing allergic lung inflammation and support clinical studies of a blocking OX40 antibody in Th2 high severe asthma patients.